Vietnam and Beyond: the Challenge to Educators - Richard A. Brosio (Educational Considerations, 1973)
"Young people must be helped…systematically [to] build their own criteria of value; for otherwise we shall have a citizenry which is condemned to operate inside another's view of reality," says this concerned educator. He spells out the challenge to society and self.